Investigations in Yeast Functional Genomics and Molecular Biology 2014
DOI: 10.1201/b16586-13
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation of Prions in Yeast

Abstract: Hundreds of RNA-binding proteins (RBPs) control diverse aspects of post-transcriptional gene regulation. To identify novel and unconventional RBPs, we probed high-density protein microarrays with fluorescently labeled RNA and selected 200 proteins that reproducibly interacted with different types of RNA from budding yeast Saccharomyces cerevisiae. Surprisingly, more than half of these proteins represent previously known enzymes, many of them acting in metabolism, providing opportunities to directly connect int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…However, recognition of cytosolic proteins for their cognate mRNAs has precedents. For example the survey of RNA binders in S. cerevisiae described above, found that 30% of RNA-binding proteins tested bound their own mRNAs, and many of these proteins were cytosolic (Scherrer et al, 2010). A similar finding was reported in survey of the RNAs bound by known RNA-binding proteins in S. cerevisiae (Hogan et al, 2008).…”
Section: The Cellular Location Of the Sec2p Interaction With Its Mrnasupporting
confidence: 71%
See 1 more Smart Citation
“…However, recognition of cytosolic proteins for their cognate mRNAs has precedents. For example the survey of RNA binders in S. cerevisiae described above, found that 30% of RNA-binding proteins tested bound their own mRNAs, and many of these proteins were cytosolic (Scherrer et al, 2010). A similar finding was reported in survey of the RNAs bound by known RNA-binding proteins in S. cerevisiae (Hogan et al, 2008).…”
Section: The Cellular Location Of the Sec2p Interaction With Its Mrnasupporting
confidence: 71%
“…To our knowledge, the identification of GEF as an RNA-binding protein is unique among fungi. However, several Arf GTPases have been shown to bind mRNA in S. cerevisiae (Trautwein et al, 2004;Scherrer et al, 2010) and in mammalian cells, Arf-GEF1 was identified as a candidate RNA-binding protein in the Atlas of mRNA-binding proteins (Castello et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These include other preribosomal, polysomal, nucleolar, and translation associated proteins (Figure 2A, Table S3). In addition to their known targets of rRNA, tRNA or snoRNA for ribosome biogenesis, or their role in other cellular functions such as vacuolar trafficking or glycolysis, many of the 120 non-ribosomal RBP have recently been found to bind mRNA (Hogan et al 2008; Scherrer et al 2010; Tsvetanova et al 2010; Mitchell et al 2013). Thus, affinity purifying Dhh1 under native condition has allowed us to isolate the core PB subcomplexes along with many PB/SG associated proteins known for their role in mRNA binding and translational functions.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, protein microarrays have been recently used to test the binding of proteins with a specific RNA in vitro. 43,44 The RNA is fluorescently labeled and hybridized on a protein chip. This method allows the screening of thousands of proteins in less than a day, and relatively small amounts of RNA are required.…”
Section: Rna-centric Approachesmentioning
confidence: 99%